Relation between chest compression rate and depth: the ENFONCE Study. (October 2021) - Agostinucci, Jean-Marc; Weisslinger, Lisa; Marzouk, Nessrine; Zouaghi, Haroun; Ekpe, Kenneth; Genthillomme, Angelie; Adnet, Frédéric; Guenin, Aurélien; Reuter, Paul-Georges; Lapostolle, Frédéric
Abstract : Introduction: Chest compressions are the cornerstone of cardiopulmonary resuscitation. The recent International Liaison Committee on Resuscitation guidelines recommend increasing the rate and the depth of chest compressions, to 100–120/min and 5–6 cm, based on theoretical arguments and observational studies. We hypothesized that an increased chest compressions rate could decrease chest compressions depth. Methods: Operators were asked to perform continuous chest compressions on a mannequin. Chest compressions rate and depth were collected. The ratio of chest compressions compliance to the guidelines, that is rate 100–120/min and depth 5–6 cm, was calculated. Results: In total 951 sequences of chest compressions were studied. Median chest compressions rate: 114 (104–130)/min. Median chest compressions depth: 4.5 (3.4–5.3) cm. Correlation between rate and depth: low (R 2  = 0.12). Chest compressions in compliance with the recommended rate: 434 (46%). Rate >120/min in 285 (30%) cases and <100/min in 223 (23%) cases. Chest compressions in compliance with the recommended depth: 286 (30%). Depth >6 cm in 50 (5%) cases and <5 cm in 621 (65%) cases. Finally, chest compressions were in compliance with the guidelines for both rate and depth in 141 (15%) cases. The ratio of chest compressions in compliance with the recommended depth significantly decreased with the increase of the rate: 40% for a rate <100/min, 32% for a rate in the target (100–120/min) and 18% for a rate >100/min ( P  < 0.0001). Discussion: The ratio of chest compressions in compliance with the recommended rate and depth was as low as 15%. The rate of chest compressions in compliance with the recommended depth significantly decreased when the chest compressions rate increased. To reach both recommended rate and depth seems illusive.